HUBUNGAN TINGKAT PENGETAHUAN DENGAN MOTIVASI MELAKUKAN IVA TEST PADA IBU RUMAH TANGGA DI DESA SAKUNG KECAMATAN DELANGGU KABUPATEN KLATEN - Aminingsih Sri; Marta Putri Budiningtyas (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
Background. Interviews conducted five housewife in the village Sakungregarding the level of knowledge about cervical cancer, showed 2 of 5 housewifein the village Sakung know about cervical cancer, while 3 Housewives do notknow well about cervical cancer and even some mothers did not know aboutcervical cancer and examination of IVA Test as early detection of cervical cancer,there are some mothers who want to do the IVA Test but in the nearest healthcenter are no programs for the examination of IVA Test. According to Purnomo(2009) for a positive thing, especially for the future of reproductive health shouldconduct checks as early as possible so that its impact can be quickly resolvedObjective: To determine the relationship of the level of knowledge about cervicalcancer with the motivation of doing IVA Test on a housewife in the village SakungDelanggu District of Klaten District.Methods: This study was a cross sectional study design measurements orobservations made simultaneously at any one time (one time). Number ofsamples of this study 86 housewife.Results: The results of chi-square analysis using SPSS version 18.0 with p =0.05 p = 0,000 is obtained so that the value of p <0.05, which means Haaccepted.Conclusion: There is a relationship with the motivation level of knowledge didIVA Test housewives in the village Sakung Delanggu District SubdistrictKlaten.with p = 0.000.Keywords: The level of knowledge, motivation did IVA Test, Cervical Cancer